Karakterisasi DNA Mikrobiota Usus Bayi pada Persalinan Normal yang diberi ASI dan Susu Formula - Mudyawati Kamaruddin; Nurhidayat Triananinsi; Nurqalbi Sampara; Sumarni Sumarni; Minarti Minarti; A. Maya RA (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Breast milk is the best source of nutrition because it contains a variety of healthy compounds and immunity. Several studies of gut microbiota has proven its important role in the development of the immune system. This study aims to characterize the gut microbiota of babies born normally with breastfeeding and formula milk. This research using cross sectional study design with purposive sampling as sampling technique. Samples used were babies born normally as many as 30 infants that divided into two groups namely infants who given breast milk and combinated breastfeeding and formulamilk of 15 infants each. Stool samples were taken by swab technique, the DNA was extracted using a DNA kit continued DNA amplification by PCR with 16SrRNA universal primers then DNA sequencing. Data from DNA sequencer analized using a software of MEGA5 and BLAST attained on the NCBI link. The result showed that the group of infants who were breastfed plus formula milk had more varied intestinal microbiota than the group of infants who were only given breast milk. It can be concluded that intestinal microbiota that dominates the intestines of infants who are given breast milk can be a probiotic in the growth of the baby and the development of the immune system.